A Multilaboratory Toxicological Assessment of a Panel of 10 Engineered Nanomaterials to Human Health—ENPRA Project—The Highlights, Limitations, and Current and Future Challenges. (2nd January 2016) - Kermanizadeh, Ali; Gosens, Ilse; MacCalman, Laura; Johnston, Helinor; Danielsen, Pernille H.; Jacobsen, Nicklas R.; Lenz, Anke-Gabriele; Fernandes, Teresa; Schins, Roel P. F.; Cassee, Flemming R.; Wallin, Håkan; Kreyling, Wolfgang; et al.
ABSTRACT: ENPRA was one of the earlier multidisciplinary European Commission FP7-funded projects aiming to evaluate the risks associated with nanomaterial (NM) exposure on human health across pulmonary, cardiovascular, hepatic, renal, and developmental systems. The outputs from this project have formed the basis of this review. A retrospective interpretation of the findings across a wide range of in vitro and in vivo studies was performed to identify the main highlights from the project. In particular, focus was placed on informing what advances were made in the hazard assessment of NM, as well as offering some suggestions on the future of "nanotoxicology research" based on these observations, shortcomings, and lessons learned from the project. A number of issues related to the hazard assessment of NM are discussed in detail and include use of appropriate NM for nanotoxicology investigations; characterization and dispersion of NM; use of appropriate doses for all related investigations; need for the correct choice of experimental models for risk assessment purposes; and full understanding of the test systems and correct interpretation of data generated from in vitro and in vivo systems. It is hoped that this review may assist in providing information in the implementation of guidelines, model systems, validation of assessment methodology, and integrated testing approaches for risk assessment of NM. It is vital to learn from ongoing and/or completed studies to avoid unnecessary duplication and offer suggestions that might improve different aspects of experimental design.